Making Union Membership the Default Option in Canada: Would It Be Supported and Effective? - Harcourt, Mark; Gall, Gregor; Wilson, Margaret (Relations industrielles / Industrial Relations, 2022)
SummaryIncome inequality has risen in Canada with the decline in union density and, thus, in union influence. Both trends have occasioned various proposals to reform federal and provincial labour relations systems, especially those aspects concerning certification. However, most proposals have been based on minor modifications to the Wagner Model of exclusive, majoritarian representation. To realize the full potential of these reform proposals, including, importantly, the likes of ‘broad-based bargaining,’ we contend that union membership should be the default option for new workers. Such a change would enable these proposals to increase absolute and relative levels of union membership, thereby providing the organizing resources (financial, human) required for much higher levels of union influence. In this study, we show that those living in Canada generally support union membership by default and would not opt out afterwards. We believe this popular support justifies making union membership automatic for new workers.AbstractUnion density has declined in Canada and, with it, wage inequality has risen, occasioning various proposals to reform the certification systems operating provincially and federally. However, such proposals are ordinarily based on only minor changes to the Wagner Model. We contend that to realize the full potential of these proposals, union membership by default is required to increase union membership levels. In this study, we show that those living in Canada generally support union membership as the default option and would not opt out afterwards. We believe this popular support justifies more comprehensive study of the proposal to make union membership automatic for new workers.